Soft methods in the prediction and identification analysis of axially compressed R/C columns - Ziaja, Dominika; Waszczyszyn, Zenon (Computer Assisted Methods in Engineering and Science, 2017)
Two problems are presented in the paper concerning axial loading of R/C columns: I) prediction of critical loads, II) identification of concrete strength. The problems were analyzed by two methods: A) Gaussian Processes Method, B) Advanced Back-Propagation Neural Network. The results of the numerical analysis are discussed with respect to numerical efficiency of the applied methods.